2012
DOI: 10.1177/0898010112464121
|View full text |Cite
|
Sign up to set email alerts
|

Acute Care Nurses’ Spiritual Care Practices

Abstract: The purpose of this study was to identify barriers in providing spiritual care to hospitalized patients. A convenience sample (N = 271) was recruited at an academic medical center in New York City for an exploratory, descriptive questionnaire. The Spiritual Care Practice (SCP) questionnaire assesses spiritual care practices and perceived barriers to spiritual care. The SCP determines the percentage that provides spiritual support and perceived barriers inhibiting spiritual care. The participation rate was 44.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
101
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 30 publications
10
101
1
5
Order By: Relevance
“…These programs could further support and sustain novice nurses with considering the significance of spirituality. [28] Being present and listening to patients was clearly identified as a struggle by these nurses. A possible approach to empower nurses and increase spiritual care is through education and providing skills to practice holistically.…”
Section: Expressions Of Spiritual Care and Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…These programs could further support and sustain novice nurses with considering the significance of spirituality. [28] Being present and listening to patients was clearly identified as a struggle by these nurses. A possible approach to empower nurses and increase spiritual care is through education and providing skills to practice holistically.…”
Section: Expressions Of Spiritual Care and Interventionsmentioning
confidence: 99%
“…Situational barriers to providing spiritual care include insufficient time, [28] the be-lief that patient's spirituality is personal, complexity in distinguishing proselytizing from spiritual care, and difficulty in meeting needs when spiritual beliefs were not the same as the nurse's beliefs. Additionally, studies indicate that some of the other barriers include lack of colleague and management backing, lack of privacy to sustain patients' wishes, and insufficient education.…”
Section: Nursing Rolementioning
confidence: 99%
See 1 more Smart Citation
“…Our findings support existing evidence that nurses do not feel completely prepared or comfortable in attending to the spiritual aspect of patient care. 2,11 The nurses in our study perceived a need for further education or readily available resources to assist them in providing culturally competent spiritual care.…”
Section: Discussionmentioning
confidence: 99%
“…1 To provide holistic care, nurses must be prepared to address all dimensions, including spiritual dimensions. Research 2,3 has indicated that nurses often feel unprepared to meet the spiritual needs of their patients. A review of definitions in the literature revealed no common or universally accepted definition for the term spirituality.…”
mentioning
confidence: 99%